Differences on the Wheat Trait Preferences Between Women and Men from the Same Household - Gartaula, Hom Nath; Atreya, Kishor; Konath, Noufa C.; Mondal, Suchismita; Singh, Ravi P. (2023)
Public breeding programs rarely consider farmers' needs and preferences, especially gender based preferences, in developing improved varieties for farmers. Our research examined how personal, household, agronomic and ecological characteristics of wheat-growers in Bihar, India, affect female and male farmers' wheat trait choices. A total of 1,003 households with both male and female from the same household were interviewed. The results imply that gender influences the preferences for wheat traits. Some traits are favored by both men and women, however in other instances there are striking disparities. Men chose wheat varieties that are well adapted to extreme climate conditions, have a higher grain yield, and produce chapatis with a superior taste, while women preferred wheat types with superior chapati making quality, higher grain yield, and high market prices. Other socioeconomic, agronomic, cultural, and geolocation factors also had a considerable impact on trait preferences. These human dimensions of traits preferred by women and men farmers may be considered when selecting combinations of traits to develop breeding product profiles for certain market segments.